Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/sms.12305
|View full text |Cite
|
Sign up to set email alerts
|

Exercise in youth: High bone mass, large bone size, and low fracture risk in old age

Abstract: Physical activity is favorable for peak bone mass but if the skeletal benefits remain and influence fracture risk in old age is debated. In a cross-sectional controlled mixed model design, we compared dual X-ray absorptiometry-derived bone mineral density (BMD) and bone size in 193 active and retired male elite soccer players and 280 controls, with duplicate measurements of the same individual done a mean 5 years apart. To evaluate lifetime fractures, we used a retrospective controlled study design in 397 reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 32 publications
1
52
0
1
Order By: Relevance
“…Children with increased PA also had higher gains in muscle strength, which points to an even larger possible fracture risk reduction, since improved neuromuscular function is associated with a low fall risk . As other studies have also shown that PA associated skeletal benefits remain long after any reduction of activity , it seems possible that our intervention programme may also reduce the fracture risk in adulthood. The POP cohort study has previously found an association between years of PA intervention and a reduction in fracture risk .…”
Section: Discussionmentioning
confidence: 64%
“…Children with increased PA also had higher gains in muscle strength, which points to an even larger possible fracture risk reduction, since improved neuromuscular function is associated with a low fall risk . As other studies have also shown that PA associated skeletal benefits remain long after any reduction of activity , it seems possible that our intervention programme may also reduce the fracture risk in adulthood. The POP cohort study has previously found an association between years of PA intervention and a reduction in fracture risk .…”
Section: Discussionmentioning
confidence: 64%
“…Exactly how long time of PA that is needed to receive lower fracture risk is not determined, but we could in our study only find effects after 8 years of intervention. Other studies have shown that fracture incidence is low in former athletes [8][9][10][11] and that PA-induced skeletal benefits are partly retained long term after reduced activity level. 9 23 24 We therefore speculate that our school-based intervention programme could result in lower fracture risk in adulthood and old age, but future prospective studies are needed to verify or reject this hypothesis.…”
Section: Discussionmentioning
confidence: 96%
“…[5][6][7] Other studies have found that induced skeletal benefits in adolescence and young adulthood are positively correlated with low fracture risk later in adulthood. [8][9][10][11] There are no studies however that has shown that PA-induced gains in musculoskeletal function in childhood result in lower fracture risk. Instead, increased PA in childhood has actually been found to initially increase the fracture risk, 3 12 possibly because any beneficial gains in bone mass and muscle function are only reached after some time of participation in PA.…”
Section: Introductionmentioning
confidence: 99%
“…The variation that gets the most attention is associated with clinically relevant bone loss: osteopenia and osteoporosis (Nelson et al, 2011; Warden et al, 2013; Sheu et al, 2014; Shin et al, 2014; Zhou et al, 2014). The etiology of low bone mass in late adulthood is to some degree linked to the acquisition of peak bone mass in youth, which appears to be highly heritable (Burnham and Leonard, 2008), but is also influenced by environmental factors (Tveit et al, 2015; Weaver, 2015). The dynamics of bone maintenance are complex and are important to adult health.…”
mentioning
confidence: 99%